2011
DOI: 10.1007/8904_2011_54
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcome of Propionic Aciduria Treated at Presentation with N-Carbamylglutamate: A Retrospective Review of Four Patients

Abstract: N-carbamylglutamate (NCG) has been reported to decrease ammonia levels in patients with propionic aciduria (PA) and methylmalonic aciduria (MMA), but reports on clinical outcomes remain scant. Here, we report a retrospective series of four patients with neonatal PA treated with NCG at presentation. Patients presented between 2 and 9 days of age and peak plasma ammonia ranged from 524 to 1,572 mM. Patients received bolus (30-200 mg/kg) and sustaining (115-300 mg/kg per day) doses of NCG in addition to a standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Most published reports on neonatal patients with MMA or PA describe carglumic acid doses ranging from 100 to 250 mg/kg bw resulting in a rapid decrease of plasma ammonia levels [26,27,29,51,52,[65][66][67]. In a single MMA patient with neonatal hyperammonemia unresponsive to standard treatment, plasma ammonia levels after a loading dose of carglumic acid (70 mg/kg) dropped by 300 µmol/l/h and normalized after 3 h to <100 µmol/l [29].…”
Section: Use In Acute Hyperammonemia Secondary To Organic Aciduriasmentioning
confidence: 97%
See 1 more Smart Citation
“…Most published reports on neonatal patients with MMA or PA describe carglumic acid doses ranging from 100 to 250 mg/kg bw resulting in a rapid decrease of plasma ammonia levels [26,27,29,51,52,[65][66][67]. In a single MMA patient with neonatal hyperammonemia unresponsive to standard treatment, plasma ammonia levels after a loading dose of carglumic acid (70 mg/kg) dropped by 300 µmol/l/h and normalized after 3 h to <100 µmol/l [29].…”
Section: Use In Acute Hyperammonemia Secondary To Organic Aciduriasmentioning
confidence: 97%
“…The use of carglumic acid for treatment of acute hyperammonemia secondary to organic acidurias has been reported in a small number of case reports [26][27][28][29][30]51,52,65] and was also discussed based on isotope studies in healthy volunteers [64]. Most published reports on neonatal patients with MMA or PA describe carglumic acid doses ranging from 100 to 250 mg/kg bw resulting in a rapid decrease of plasma ammonia levels [26,27,29,51,52,[65][66][67].…”
Section: Use In Acute Hyperammonemia Secondary To Organic Aciduriasmentioning
confidence: 99%
“…NCG has recently been used as part of a multiple treatment strategy for hyperammonaemia in MMA [5,6,7] and in other classical organic acidurias such as propionic aciduria [6,7,11,12,13,14] and isovaleric aciduria [15]. Kasapkara et al [15] reported on the use of NCG in the treatment of hyperammonaemia in a 3-day-old neonate with decompensated isovaleric aciduria with a single dose of NCG 150 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of these medications in organic acidemias is controversial. While no controlled studies have been performed, some reported cases suggest that scavenger medications may have limited effectiveness to lower ammonia levels during acute hyperammonemic crisis in children in PA [4345]. Therefore, currently proposed guidelines for the management of MMA and PA caution that phenylbutyrate/phenylacetate should be used with extreme caution and should be discontinued once the diagnosis of MMA and PA is established [46].…”
Section: Further Characterization Of Efficacy Of Ncg In Various Comentioning
confidence: 99%